Naturalness, string landscape and multiverse: a modern introduction with exercises - Hebecker, Arthur (Springer, 2021)
Reminder of SM, EFTs and a naive view of the hierarchy and cosmological constant problems -- Basics of SUSY and SUGRA -- A crash course on strings and how to derive the 10d supergravity action for Type IIB -- Kaluza-Klein compactifications -- Calabi-Yau compactifications -- Flux-landscape in a toy-model -- Flux-landscape in Calabi-Yaus -- Moduli-stabilization and uplift -- Landscape-statistics -- Eternal inflation -- The Measure Problem.
Keywords: Supergravitation; Supersymmetrie; Stringtheorie